دراسة عناصر السرد في رواية "الوخز" لحسين العبري - العجمي إسماعيل بن مبارك بن سالم (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The novel "Al-Wakhz" by the author Hussein Al-Abri is considered one of the important Omani novels that focuses on the political aspect by investigating the subject of the prohibited secret organization that was uncovered by the state. This research aims to study the narrative elements in the novel "Al-Wakhz" and how the narrative elements are employed: the omniscient narrator, and the character in terms of the language of the educated man, the elderly man, and the investigator, as well as the technique of internal and external dialogue among the characters, the event, and the description. We provided examples of the narrative elements through the novel.